2018
DOI: 10.1186/s12891-018-2278-1
|View full text |Cite
|
Sign up to set email alerts
|

Distal biceps tendon rupture: advantages and drawbacks of the anatomical reinsertion with a modified double incision approach

Abstract: BackgroundDistal biceps tendon rupture occurs more often in middle-aged male population, involving the dominant arm. In this retrospective study, it’s been described the occurrence of the most frequent adverse events and the clinical outcomes of patients undergoing surgical repair of distal biceps tendon rupture with the modified Morrey’s double-incision approach, to determine better indications for patients with acute tendon injury.MethodsSixty-three patients with acute distal biceps tendon rupture treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
1
18
0
3
Order By: Relevance
“…Even though the surgical treatment is now considered the treatment of choice, there is not a general agreement on which is the best surgical approach. Some authors prefer the single anterior approach (16)(17)(18); while others prefer the Boyd and Anderson double-incision technique (1,10,11,19). Even though the two-incision technique limits the volar surgical dissection, it has been associated with important complications including proximal radio-ulnar synostosis (20), formation of proximal radio-ulnar calcifications and lesions on the posterior interosseous nerve (21).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the surgical treatment is now considered the treatment of choice, there is not a general agreement on which is the best surgical approach. Some authors prefer the single anterior approach (16)(17)(18); while others prefer the Boyd and Anderson double-incision technique (1,10,11,19). Even though the two-incision technique limits the volar surgical dissection, it has been associated with important complications including proximal radio-ulnar synostosis (20), formation of proximal radio-ulnar calcifications and lesions on the posterior interosseous nerve (21).…”
Section: Discussionmentioning
confidence: 99%
“…According to Kodde et al [20] the double-incision approach had significantly fewer complications than the single-incision anterior approach in their latest systematic review of 40 studies. However, the clinical outcome remains controversial [21,22], as some authors reported a significantly greater proportion of unsatisfactory results than with single-incision repair [23]. In the only randomized controlled trial to this topic, no significant differences in outcomes between the single-and doubleincision distal biceps repair techniques other than a 10% advantage in final flexion strength with the latter could be shown [9].…”
Section: Discussionmentioning
confidence: 99%
“…(47) Broken tendons are subject to several treatment techniques: one cut technique (use of seam anchors), two-cut technique (using bone tunnels), biotendinosis screw for fixation and endobuttons. [4,9,10,17,27,41,42]. Different methods of double incision (standard and modified) are characterized by a different dimension of showing the ulnar periosteum.…”
Section: Anatomic Studymentioning
confidence: 99%
“…It turned out that against the induction of nerve palsy (radial or lateral antebrachial cutaneous nerve) nor the heterotopic ossification does not protect the anterior small incision of the cubital fossa with the execution of muscle splitting technique. [42].…”
Section: Anatomic Studymentioning
confidence: 99%